Program Pendampingan Implementasi ISAK 35 Dengan Pembuatan Kebijakan Akuntansi Sebagai Pedoman Akuntansi Pondok Pesantren di Kota Batam - Arniati Arniati; Danar Irianto; Doni Putra Utama; Muhammad Irsyad Halim; Muhammad Ramadhan Slamet; Riri Zelmiyanti; Sinarti Sinarti (Pusat P2M Politeknik Negeri Batam, 2021)
Islamic Boarding School is one of the non-profit institutions that produces financial reports to be presented to stakeholders, there are not many resources in Islamic Boarding Schools that have expertise in accounting and finance, so that in making financial statements they often experience problems, even some who experience bankruptcy. Making the preparation of Accounting Policies is made to provide guidance to Islamic boarding schools in making financial reports. The Accounting Policies provided are SAK ETAP, Components of Accounts such as Asset Accounting, Liability Accounting, Net Asset Accounting, Income and Expense Accounting, Cash Flow Accounting and Notes on Financial Statements. prepare financial reports so that the accountability and responsibility of financial statements can be better accounted for to the public. The method used is training and assistance in the preparation of financial statements based on accounting policies that have been made in accordance with ISAK 35. The Community Service Program for the Batam State Polytechnic Business Management Department has been implemented and is running well, which is followed by all Islamic Boarding Schools in Batam City.